Keefektifan Penggunaan Media Lagu dalam Pembelajaran Menulis Puisi Siswa Kelas VIII I SMPN 1 Jember - Rohmah Juwita Sari; Anjar Putro Utomo (ScienceEdu: Jurnal Pendidikan IPA, 2019)
The purposes of this study were to describe the effectiveness of using song media in poetry writing skill for VIII I SMP N 1 Jember students. The data of this study were from the result of poetry writing skill pre-test and post-test by using song media in VIII I SMP N 1 Jember. Based on the result of data analysis and discussion, it can be concluded that (1) poetry writing skill of VIII I SMP N 1 Jember students without using song media with average 58,33, and (2) poetry writing skill VIII I SMP N 1 Jember students by using song media with average 72,26.